Ideały społeczno-wychowawcze z perspektywy pedagogiki społecznej i władzy politycznej - Pilch, Tadeusz (Pedagogika Społeczna Nova, 2021)
The aim of this article is to show the contradiction between establishing social pedagogy as a scientific discipline and equipping the humans, especially youth, with a system of humanitarian values and at the same time, initiating practical activities aimed at improving the material conditions of life. The opposite of these humanistic aspirations of the scientific discipline is the destructive action of political power based on malicious intentions, subordinating to its power, often authoritarian, the life and behaviors of citizens. The government rejects his vocation to serve the common good and the country’s develop- ment; and focuses on dominating all manifestations of collective and individual life. This striving for power reduces civil liberties and rights, divide society into hostile interest groups, and lead to abuse of violence and economic crisis. An additional nuisance for the society is the drastic neglect of social welfare, the disorganization of the infrastructure serving the public and the general disorganization of collective life. In this form, power can only be abolished.